2019
DOI: 10.21273/hortsci14271-19
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Integrating Biochar and Deficit Irrigation Strategies for Sustaining Vegetable Production in Water-limited Regions: A Review

Abstract: Water shortage is one of the major challenges faced by the current agricultural systems worldwide, especially in arid and semi-arid regions. Deficit irrigation (DI), a water-saving strategy of applying less water than crop evapotranspiration (ETc) demands, has been extensively investigated in different crops, including water-intensive vegetables. The DI strategies such as regulated deficit irrigation (RDI) and partial root zone drying (PRD) generally increase water use efficiency (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 49 publications
(76 reference statements)
2
32
0
Order By: Relevance
“…In another study, conventional furrow irrigation was effective for growth and yield parameters of potato; indicating differences between irrigation methods (Verma et al, 2017). The addition of biochar under deficit irrigation helped to compensate for yield losses of vegetables and further enhanced water use efficiency (Singh et al, 2019). We also found that at least one irrigation could be cut off with the application of biochar.…”
Section: Interaction Effectmentioning
confidence: 60%
“…In another study, conventional furrow irrigation was effective for growth and yield parameters of potato; indicating differences between irrigation methods (Verma et al, 2017). The addition of biochar under deficit irrigation helped to compensate for yield losses of vegetables and further enhanced water use efficiency (Singh et al, 2019). We also found that at least one irrigation could be cut off with the application of biochar.…”
Section: Interaction Effectmentioning
confidence: 60%
“…However, the majority of these studies investigated cereals crops and effects of biochar on vegetable crops are less reported, e.g., [38,39]. A review by Singh et al [40] reported 10 studies on the effects of biochar on vegetables and found that nine of these studies showed that biochar enhanced vegetable growth, yield and water use efferences. Biochar enhanced tomato growth and soil fertility but did not affect the quality and yield [41].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that drip irrigation and infiltration irrigation could save more than 50% water, yield improvement and increase water use efficiency by 2-5 times (Hanson and May, 2006;Karlberg and Vries, 2004;Song et al, 2009). New water-saving irrigation technologies, such as drip irrigation and infiltration irrigation, have good water-saving and production increasing effects, but they need to install supporting pressure equipment, water pipeline and emitter, which increased the cost and need high water quality requirements (Li et al, 2019;Mostafa et al, 2018;Singh et al, 2019) and ultimately limit the application of water-saving irrigation technology in agricultural production. The perforated membrane is used to replace the pipes, such as drip irrigation belt and drip irrigation pipe and the perforated membrane is laid in the ridged ditch and then a layer of plastic film is covered on it (Wang et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%